THE INFLUENCE OF SEATING ARRANGEMENT TOWARD STUDENTS’ PARTICIPATION IN LEARNING ENGLISH AT SMK NEGERI 2 BARRU - St. Aminah A; Ummi Khaerati Syam; Nunung Anugrawati (FKIP Unismuh Makassar, 2021)
The objective of this research was to know the influence of seating arrangement toward students’ participation in learning English, focused on clusters model and pairs model of seating arrangement at the tenth grade students of SMK Negeri 2 Barru. The method of this research was descriptive qualitative method. Collecting the data of this research used observation checklist and video recorded during learning process in the classroom. The result of this research found that clusters model made mostly the students unconcerned in responded the material caused of the group consisted more than two students. Meanwhile, pairs model made the students more enthusiastic in responded the material caused of the students’ engagement is tied together. It could be seen in the percentage of students’ activeness which indicated that there was 64.6% students’ participation in clusters model and 77.5 % students’ partisipation in pairs model of seating arrangement during in learning process. It means that, every seating arrangement had different influence toward students’ active participation in learning English at the classroom.